CLEMENTS, Andrea D.; HUMANO-UNTERRAINER, Friedrich y COOK, Christopher C. H.-Eds. (2023) Human connection as a treatment for addiction. Frontiers Media SA. Lausanne. Pp. 250 - López Ramírez, Enrique; García-Montalvo, Ivan Antonio; García-Montalvo, Gildardo Oswaldo (Espacio Abierto, 2024)
.